THE ROLE OF USING ISLAMIC FINANCE TO BOOST INFRASTRUCTURE DEVELOPMENT FOR SUSTAINABLE ECONOMIC GROWTH (Journal of Research Administration, 2023)
This study aims to analyze the role of applying Islamic finance practices to boost investment in good and sustainable infrastructure, based on partnerships between the public and private sectors, and discusses the extent to which this contributes to achieving sustainable economic growth. Our study was based on a qualitative analysis of Islamic financial products and their uses for investment in infrastructure in a group of countries that are witnessing development in the Islamic financial industry, especially developing ones, as well as an analysis of the quantitative development of Islamic financial institutions and capital markets based on various indicators calculated regularly, in particular Refinitiv's IFDI Index and Islamic Capital Markets Product Ratings, analyzing the growth and evolution of Islamic financial industry assets, looking at all its sub-sectors, and reviewing their quantitative dimensions in terms of size and performance. In conclusion, we found that Islamic finance is a viable option for sustainable infrastructure development. With the right strategies, it can contribute to meeting investment needs and fostering inclusive growth. To support sustainable growth through Islamic finance, collaboration and innovation should be fostered by embracing standardization, innovation, and digitization. Knowledge about Islamic finance in infrastructure projects is also crucial.Keywords: Islamic finance, infrastructure development, sustainable economic growth.